Separation behavior of sieved endosperm-enriched oat fractions via tribo-electrostatic approach. (August 2022) - Konakbayeva, Dinara; Kuspangaliyeva, Botagoz; Rajabzadeh, Amin Reza; Tabtabaei, Solmaz
Abstract: Endosperm-enriched oat fraction passed through 106-μm aperture size sieving of oat groats was further processed by dry and chemical-free tribo-electrostatic separation approach for protein enrichment. The sieved oat flour consisting of both bran and endosperm particles was fluidized in dry air to be tribo-charged in a polytetrafluoroethylene (PTFE) tube before being separated under an external electric field into protein-rich and protein-depleted fractions. The effects of airflow rate and electric field strength were assessed by conducting fifteen tribo-electrostatic separations at five different plate voltages of ±1, ±3, ±7, ±12, and ± 15 kV, as well as three different airflow rates of 7, 10, and 14 l per minute (LPM), providing laminar, transient, and turbulent conditions in the tribo-charger tube, respectively. All fractions attracted to the negatively charged plate (i.e., NCP fraction) were enriched in protein. However, the fractions absorbed on the positively charged plate (PCP fraction) or collected by gravity at the bottom of the separation chamber (i.e., CB fraction) were all depleted of proteins. Higher protein enrichments were observed for NCP fractions at laminar airflow rate, where the lowest yields and protein separation efficiencies were obtained. Increasing plate voltages slightly reduced the NCP fractions' protein content but significantly improved their yields and protein separation efficiencies. Therefore, a laminar airflow rate of 7 LPM and a high plate voltage of ±12 kV was selected as the best separation conditions for sieved oat flour. The SEM images of the NCP fraction obtained at 7 LPM and ± 12 kV showed the presence of bran and endosperm particles, while the PCP and CB fractions were depleted of bran particles. The full compositional analysis of the fractions produced at 7 LPM and ± 12 kV conditions showed the highest percentage of dietary fiber content in the PCP fraction. A negative correlation was observed between the protein content and mean particle size (D50 ) of the electrostatically separated fractions at the laminar and transient airflow rates. However, the protein-rich NCP fractions had the largest particle sizes at the turbulent airflow rate due to particle agglomeration and intense particle-particle interactions. An indirect offline approach was adapted to assess the charging behavior of all electrostatically separated fractions as functions of their protein content and particle sizes. All NCP fractions acquired higher charge density values than other fractions, which could be attributed to their higher protein contents. An online tribo-charge analysis method should be developed to assess the particle-particle interactions in the tribo-charger tube during electrostatic separation. Highlights: Sieved endosperm-rich oat flour was fractionated via tribo-electrostatic separation. The effect of airflow rate and plate voltage was assessed on oat protein enrichment. A laminar flow and the high voltage produced protein-rich fractions with high yields. Protein and particle size of the fractions were inversely correlated at laminar flow. The tribo-charging behavior of the fractions was evaluated based on protein content.